IMPACT OF GLOBALIZATION PROCESSES ON RUSSIAN ECONOMY - Inessa Penkova; Ovsanna Dzhavadova (Вестник Северо-Кавказского федерального университета, 2022)
The article aims at revealing the degree and power of the worldwide globalization processes influence on Russian national economy. In the process of research, the tasks were settled to define and analyze the key indicators characterizing the principal effects of globalization. Basing on the proposed model, the impact of globalization processes on the Russian economy is calculated. It is proved that the transnationalization index in Russia does not demonstrate steady dynamics. This is explained by the volatility of foreign direct investment, which directly depends on political conditions, the desire of residents to keep money within the state, the macroeconomic situation and relations with the main trading partners. The volume of exports of goods, services and capital are key indicators to determine the economic growth rate in the Russia. An increase in the real effective exchange rate of the ruble leads to a decrease in the gross domestic product.